2018
DOI: 10.1158/1940-6207.capr-18-0159
|View full text |Cite|
|
Sign up to set email alerts
|

Sex-Specific Association between Family History of Diabetes and Risk of Colorectal Cancer: Two Prospective Cohort Studies

Abstract: Type 2 diabetes (T2D) is associated with increased risk of colorectal cancer. It remains unclear whether family history of diabetes influences colorectal cancer risk and relevant biomarkers. We followed 101,323 women from the Nurses' Health Study (1982-2012) and 48,542 men from the Health Professionals Follow-up Study (1988-2012), free of cancer and inflammatory bowel disease at baseline. Participants reported whether any of their first-degree family members ever had diabetes in multiple questionnaires adminis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Bauer et al 39 investigated familial aggregation of diabetes and colorectal neoplasia, and found positive associations between familial diabetes and adenomatous polyps or CRC. Ma et al 17 reported in 2018 that family history of diabetes is associated with risk of CRC in a sex-specific manner, and that the relationship is more pronounced in patients under 60 years, and only significant in males. We found this feature in both sexes with YOCRC, however, the numbers were low and hence it is not possible to confirm this observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer et al 39 investigated familial aggregation of diabetes and colorectal neoplasia, and found positive associations between familial diabetes and adenomatous polyps or CRC. Ma et al 17 reported in 2018 that family history of diabetes is associated with risk of CRC in a sex-specific manner, and that the relationship is more pronounced in patients under 60 years, and only significant in males. We found this feature in both sexes with YOCRC, however, the numbers were low and hence it is not possible to confirm this observation.…”
Section: Resultsmentioning
confidence: 99%
“…Although the link between CRC and T2D has been frequently reported in studies, 16 the association between personal and/or family history of T2D and YOCRC has not been widely investigated. 17 The aim of this study was to investigate whether personal history T2D was associated with YOCRC.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies obtained, however, opposite conclusions, with low leptin levels in patients with CRC [9–13], whereas certain investigators did not observe significant CRC-related changes of leptin [4,14] or adiponectin [17,18]. This discordance may be caused by different localizations of CRC in study-enrolled patients [18,19,21,22], by cancer staging [8,11,14] and multicenter approach [1923].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear whether modifications in adipokine levels described in patients with digestive cancer represent a causative link or are merely an adaptive epiphenomenon [20]. Finally, the contrasting data described in the literature may be caused by the heterogeneity of studied groups with respect to tumor localization [3,9, 21,22], gender [7,23], weight modification [3,9], disease severity [8], chemotherapy [24] or due to statistical complexity caused by multicentricity of the study or complex metaanalysis [3,4,18,21,22]. In order to avoid these variations, one needs to choose a more homogenous series, in a single location at similar stages.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A previous study suggested that patients with an FHD tended to have a higher risk of colorectal cancer (men, HR=1.19, 95% CI 1.04 to 1.36; women, HR=1.06, 95% CI 0.96 to 1.17) than those without an FHD. 5 Moreover, an FHD also plays an important role in the prevalence of pre-diabetes, 7 diabetes risk, 8 glycaemic control, 9 and insulin secretion and sensitivity. 10 A multicentre study that included 8106 participants without diabetes revealed that an important risk factor for pre-diabetes (OR=1.26, 95% CI 1.14 to 1.40) was an FHD, even after adjustments for potential confounders.…”
Section: Introductionmentioning
confidence: 99%